Introducing magnetic resonance imaging into the lung cancer radiotherapy workflow – An assessment of patient experience. Issue 1 (February 2021) - Bellhouse, S.; Brown, S.; Dubec, M.; Taylor, S.; Hales, R.; Whiteside, L.; Yorke, J.; Faivre-Finn, C.
Abstract: Introduction: Magnetic resonance imaging (MRI) offers superior soft tissue contrast to computed tomography (CT), the current standard imaging modality for planning radiotherapy treatment. Improved soft tissue contrast could reduce uncertainties in identifying tumour and surrounding healthy tissues, potentially leading to improved outcomes in patients with lung cancer. This study explored patient experience of MR treatment planning scans in addition to a CT scan. Methods: Participants were recruited to the 'Magnetic Resonance Imaging for the Delineation of Organs At Risk and Target Volumes in Lung Cancer Patients (MR-Lung)' study at a UK specialist cancer centre. Participants completed their standard of care radiotherapy planning CT scan and two additional MRI scans. Baseline and post-scan questionnaires were completed assessing anxiety and claustrophobia. Motion artefact during MRI was assessed by a modified visual grading analysis. Sixteen participants completed semi-structured interviews; transcripts were analysed thematically. Results: 29 people (66% female; aged 54–89 years) participated. Nineteen participants completed all imaging and 10 participants withdrew before completion. There was minimal adverse impact on state and scan-specific anxiety levels from completing the MRI scans. Completers experienced significantly less scan-specific anxiety during MRI 1 compared to non-completers ( U = 33, z = −1.98, p < 0.05). 78% of those who withdrew during or post MRI 1 were positioned 'arms up'. Motion artefact negatively impacted image quality in 34% of scans. Participants commonly reported concerns during MRI; noise, claustrophobia and pain in upper limbs. Conclusion: Two thirds of participants tolerated two additional MR scans with minimal adverse impact on anxiety levels. Implications for practice: Patient arm positioning and comfort ought to be considered when introducing MR-Linac systems. A screening tool to identify those at high risk of non-completion should be developed.